Nos atalhos do pedir: favores, paternalismo e planejamento educacional no Ceará (1963-1982) - Guedes, Mardônio e Silva (2010)
This work aims to discuss the production of discourses on educational planning, paternalism and exchange of favors, in Ceará from 1963 to 1982. To do so, we analyzed educational programs, personal and institutional correspondence characterized by requests in the sphere of education and addressed to the political man Virgilio Távora during the time he performed the functions of Governor, Deputy and Senator in the State of Ceará. The correspondences mentioned comprise part of the documentary fund Virgilio Távora that put together the collection of the Public Archives of the State of Ceará. In the investigation of the documentary sources we approached the social tensions between planning actions of education and mails about the educational field specifically the ones pervaded by politics of favor, discourses associated to paternalism, clientele, work and professional qualification. The government educational programs concerning to the period herein focused , were collected from Menezes Pimentel Public Library heap. These documents established guidelines for the development of the educational sector and are hallmarks elements in preparing the proposed approach by this research; aiming to question the clashes built in the structure of state educational management and educational requests addressed to Virgilio Távora. The documentation referred to allowed to inquire about the discursive strategies produced on the educational field intersected by the logic of efficiency, technique and state planning, managed in Ceará during the time of this research. In the theoretical methodological universe of the investigation developed, we gave much attention to the constructions and appropriations produced by the discourses found in the documental sources, on educational planning, exchange of favors and patronage. These were the constituent elements of educational every day life in Ceará which were the subject of analysis in this paper.